Interview with Liz Millward: Why New Zealand? - Roth, Jennifer (Atlantis, 2013)
Roth joins in conversation with Liz Millward, an Associate Professor in the Women’s and Gender Studies Program at the University of Manitoba and the 2009 CWSA/ACÉF Book Prize Winner.